Analysis of Work Environment Factors, Incentives, and Job Satisfaction in Increasing the Loyalty of Indonesian Ombudsman Employees - Dharma Diani, Rinny; Sariwulan, Rd. Tuty; Aminah, Hania (IJHCM (International Journal of Human Capital Management), 2024)
Employee loyalty is a central issue in sustaining service quality and organizational stability in the public sector. In Indonesia, the urgency of this issue is reflected in the 2024 Bureaucratic Reform Report of the Ombudsman of the Republic of Indonesia (ORI), which recorded a loyalty score of only 73%, below the 80% target, along with rising turnover among Non-Civil Servant employees. Existing studies indicate that loyalty is shaped by multiple organizational factors, yet most research remains fragmented or private-sector oriented, leaving a gap in comprehensive understanding within public institutions. This study aims to conduct a systematic literature review to synthesize empirical findings on the relationship between work environment, incentives, job satisfaction, and employee loyalty in the public sector. Following the PRISMA framework, peer-reviewed articles published between 2015 and 2024 were identified through databases such as Scopus, Web of Science, and ScienceDirect. The review is designed to map research trends, assess methodological approaches, and identify consistent patterns of relationships across the four variables. The contribution of this study lies in building a solid theoretical foundation for developing an empirical model of public sector loyalty. The results are expected to enrich theoretical discourse, provide evidence-based directions for human resource management practices, and identify gaps to guide future research agendas.